Hemidactylus paucifasciatus (Squamata: Gekkonidae), a new species of large-bodied, tuberculate gecko from Northern Odisha, India - Mohapatra, Pratyush P.; Agarwal, Ishan; Mohalik, Rakesh Kumar; Dutta, Sushil K.; Khandekar, Akshay (Zootaxa, 2023)
A new Hemidactylus belonging to the H. prashadi group is described herein, based on a series of four specimens from the Chota Nagpur Plateau in northern Odisha. Hemidactylus paucifasciatus sp. nov. can be diagnosed from regional congeners by its large body size (SVL up to 117.7 mm), the number of dorsal tubercle rows at mid-body, three or four bands on the dorsum, the number of enlarged tubercles in paravertebral rows, the number of femoral pores and poreless scales separating the left and right series on the femoral-precloacal row in males, and the number of ventral scales across the belly at mid-body. A mitochondrial phylogeny demonstrates that the new species is nested within the H. triedrus complex of the northern clade within the H. prashadi group, with 16.2–16.5 % pairwise divergence in ND2 sequence data from members of the H. triedrus complex and > 21 % from other members of the prashadi group. Hemidactylus paucifasciatus sp. nov. is the first endemic gecko to be described from the Chota Nagpur Plateau.